Development of a mobile health application for those who have experienced pregnancy loss - Aoife Lynch; Sarah Meaney; Rachel Rice; Noirin Russell; Keelin O'Donoghue (Frontiers Media S.A., 2015)
Background The Pregnancy Loss Research Group at Cork University Maternity Hospital (CUMH) is a multidisciplinary team including doctors, midwives and researchers working collaboratively to provide support and information to patients bereaved by pregnancy loss, promote their emotional and physical well-being, as well as improving professional practice and facilitating research in this area. The group have developed a set of applications to disseminate professional information on pregnancy loss issues and aid their research with a mobile application (app) for data acquisition and management. Mobile apps have the capacity to gather and analyse a wealth of data and provide it to users in real time. Statistics show that the number of mobile subscriptions has increased and by the end of 2015, there will be more than 7 billion mobile cellular subscriptions in the world, corresponding to a penetration rate of 97%, up from 738 million in 2000. Mobile-broadband penetration levels are highest in Europe and the Americas, at around 78 active subscriptions per 100 inhabitants (ITU, 2015). Using mobile apps in medical research enables doctors to engage more participants in an easy and approachable way and to dramatically increase the amount of health data they can gather. Aims The aims of this project were to develop a content management system for a web and mobile apps in data acquisition and management. The app had a dual functionality as firstly it is to act as a resource for information on pregnancy loss issues on a mobile platform. Secondly the app needed to function as a research tool in allowing users to record their experience of pregnancy loss. No such app covers this topic in either Apple or Android app stores despite research indicating that most pregnant women download an average of three pregnancy apps during their gestational period (Frazer, et al, 2015). Methods and Results A professional website was created for the Pregnancy Loss Research Group to provide information relating to pregnancy loss and also the facilities at CUMH. A tailored content management system (CMS) was created to push articles written to both website and mobile platforms so they only need to update articles once with changes appearing on both platforms without having to alter any code. The app was built using the mobile development framework PhoneGap which incorporates Javascript, HTML5 and CSS. Once the app is opened articles are pulled from the database into local storage so that there are no barriers to accessing information. When the app has a network connection a function calls the articles from the database to sync with the articles in local storage. This keeps articles up to date and facilitates offline reading. Articles are accessed via a fixed navigation bar in sections that mirror the main website. The app has a separate ToolKit with sections that are only available after the app user creates a profile. The Toolkit allows the user to map and record their experience of pregnancy loss using a number of tools including diary entries and photos. Users can write a diary entry or take a photo and save to review. Once the user submits a diary entry or photo the overall sentiment, negative or positive, is calculated against a word list with related scores. Emojis included in diary entries can also be calculated in the sentiment rating so that the informal way in which app users communicate with mobile devices can be properly assessed. For additional research purposes, the mobile app also includes a number of validated psychometric scales including Edinburgh Postnatal Depression Scale, Perceived Stress Scale and Self Evaluation Scale for the users to complete. The mobile app calculates the score for each scale and the scores per scale are displayed to allow researchers to investigate the emotional wellbeing of the users. The CMS then operates as a web user interface that allows the data collected by the mobile app to be analysed. The CMS shows app activity statistics in 3D graphs highlighting individual app user activity and overall total app usage activity. Graphs display different user type, app user location, number of psychometric tests completed per month, app activity by time of the day and day of the week. Conclusion An effective method for data acquisition and management in pregnancy loss research has been created. Both the website and mobile app act as an accurate information resource. The CMS allows the group to manage and update the information on both platforms without technical knowledge of web or mobile frameworks. Data collected from app users has the potential to inform evidence based practice in the future.